World Antimalarial Resistance Network I: clinical efficacy of antimalarial drugs. - Price, R; Dorsey, G; Ashley, E; Barnes, K; Baird, J; d'Alessandro, U; Guerin, P; Laufer, M; Naidoo, I; Nosten, F; Olliaro, P; Plowe, C; et al. (2007)
The proliferation of antimalarial drug trials in the last ten years provides the opportunity to launch a concerted global surveillance effort to monitor antimalarial drug efficacy. The diversity of clinical study designs and analytical methods undermines the current ability to achieve this. The proposed World Antimalarial Resistance Network (WARN) aims to establish a comprehensive clinical database from which standardised estimates of antimalarial efficacy can be derived and monitored over time from diverse geographical and endemic regions. The emphasis of this initiative is on five key variables which define the therapeutic response. Ensuring that these data are collected at the individual patient level in a consistent format will facilitate better data management and analytical practices, and ensure that clinical data can be readily collated and made amenable for pooled analyses. Such an approach, if widely adopted will permit accurate and timely recognition of trends in drug efficacy. This will guide not only appropriate interventions to deal with established multidrug resistant strains of malaria, but also facilitate prompt action when new strains of drug resistant plasmodia first emerge. A comprehensive global database incorporating the key determinants of the clinical response with in vitro, molecular and pharmacokinetic parameters will bring together relevant data on host, drug and parasite factors that are fundamental contributors to treatment efficacy. This resource will help guide rational drug policies that optimize antimalarial drug use, in the hope that the emergence and spread of resistance to new drugs can be, if not prevented, at least delayed.